Reciprocal Prefix ko- in Loloda Language, North Halmahera - Gane, Maklon; Abdullah, Wakit; Purnanto, Dwi (Bina Nusantara University, 2019)
This research aimed to describe the morphological process which focused on reciprocal prefix ko- and to find the word class of the base word that could attach with that prefix in Loloda language. The sources of data were Loloda language used by Lolodanese in the field research. The data were clauses or sentences that contained base word with reciprocal prefix ko-. The data obtained through several methods and techniques, such as observation and conversation, elicitation technique, recording, taking notes, and introspection technique. Introspection technique was used because the researcher is the speaker of this language. The data were analyzed by a qualitative descriptive method. The researchers used morphologic perspective to analyze the data. The results show that reciprocal prefix can attach with base words that have vocal /o/ in the first syllable. Moreover, there are several categories of the base word can attach with reciprocal prefix ko- such as the verb, noun or noun phrase, adjective, and interrogative. The function of the reciprocal prefix is to form the active verb.